61.2k views
1 vote
Solve the following system by substitution:

y = -1x - 5
4x - 8y = 4

1 Answer

6 votes

Answer:

x = - 3

y = - 2

Explanation:

We have y = -1x - 5, so substitute that for y in the second equation:

4x - 8y = 4

4x - 8(-1x - 5) = 4

Now, solve for x:

4x + 8x + 40 = 4

12x + 40 = 4

12x = - 36

x = -3

Now, substitute - 3 in for x in the first equation:

y = -1x - 5 = -1(-3) - 5

y = 3 - 5

y = -2

You can check that these are right by substituting them into:

4x - 8y = 4

4(-3) - 8(-2) = 4

-12 + 16 = 4

4 = 4

So, you know that you solved correctly.

User Prajnavantha
by
6.4k points